Psycholinguistic Correlates of Progress in Literature at Russian Vocational Training School: A Snap Shot From Selected Paper - Sapitri, Putri Adrian (Universitas Lancang Kuning, 2019)
This article aims to present a little snapshot from the author's perspective as a review article paper. The research article written by Nuriakhmetov entitled “Psycholinguistic Correlates of progress in Literature of Students of Russian Vocational Training School” was selected to be the object of this study’s exploration. David Publishing published Nuriakhmetov’s article in 2012 in their Journal of Psychological Research Volume 2 Issue 12. This present article used descriptive qualitative analysis to bring about comprehension to the readers' minds. This article has seen literacy as a person's ability to handle their potential and develop their skills in processing and understanding information while carrying out reading and writing activities. This study explores how the relationship between the nature of students with each other and the ability of students with the transfer of professional disciplines including Literature, English, Russian, and Bashkir according to Nuriakhmetov’s article. The article seems to have a clear flow on how to explain these two types of education and make this journal easy to understand. Therefore, the present study sees Nuriakhmetov’s article to be replicable for similar studies in the future.